Tailoring Mid‐Gap States of Chalcogenide Glass by Pressure‐Induced Hypervalent Bonding Towards the Design of Electrical Switching Materials - Xu, Meng; Xu, Qundao; Gu, Rongchuan; Wang, Songyou; Wang, Cai‐Zhuang; Ho, Kai‐Ming; Wang, Zhongrui; Xu, Ming; Miao, Xiangshui (Advanced functional materials, 2023)
Phase change memory (PCM) and ovonic threshold switching (OTS) materials using chalcogenide glass are essential elements in advanced 3D memory chips. The mid‐gap states, induced by the disorder and defects in the glass, are the physical mechanisms of the electrical switching behavior, while the origin of these trap states is still under debate and the medium‐range clusters that break the global octet rule, such as over‐coordinated atoms, are known to be responsible in various glass. Here, it is discovered that a large fraction of over‐coordinated clusters fails to generate mid‐gap states, which are probably caused by hypervalent bonding, a multi‐centered covalent bond participated by delocalized lone‐pair electrons. This is confirmed by the pressure‐driven simulations of amorphous GeSe models, in which it is found that octahedral motifs and hypervalent bonds prevent the over‐coordinated medium‐range clusters from providing excessive electrons. In practical applications, compatible dopants can be used to change the number of hypervalent bonds, thus controlling the number of mid‐gap states and consequently the performance of PCM and OTS materials. These results reveal the origin of mid‐gap states in chalcogenide glasses, enabling extensive control in the development of pioneering electrical switching materials. The pressure‐driven ab initio molecular dynamics simulations elucidate the underlying relationship between the chemical bonding and electronic states in chalcogenide glasses. Changing the dopants and stoichiometry could tailor the hypervalent bonds and the number of defect states, thus enabling comprehensive control in the development of innovative electrical switching materials for 3D phase change memory (PCM) chips.